Hyperactive cyclic motor activity in the distal colon after colonic surgery as defined by high‐resolution colonic manometry. Issue 7 (14th April 2018) - Vather, R.; O'Grady, G.; Lin, A. Y.; Du, P.; Wells, C. I.; Rowbotham, D.; Arkwright, J.; Cheng, L. K.; Dinning, P. G.; Bissett, I. P.
Abstract : Background: Recovery after colonic surgery is invariably delayed by disturbed gut motility. It is commonly assumed that colonic motility becomes quiescent after surgery, but this hypothesis has not been evaluated rigorously. This study quantified colonic motility through the early postoperative period using high‐resolution colonic manometry. Methods: Fibre‐optic colonic manometry was performed continuously before, during and after surgery in the left colon and rectum of patients undergoing right hemicolectomy, and in healthy controls. Motor events were characterized by pattern, frequency, direction, velocity, amplitude and distance propagated. Results: Eight patients undergoing hemicolectomy and nine healthy controls were included in the study. Colonic motility became markedly hyperactive in all operated patients, consistently dominated by cyclic motor patterns. Onset of cyclic motor patterns began to a minor extent before operation, occurring with increasing intensity nearer the time of surgery; the mean(s.d.) active duration was 12(7) per cent over 3 h before operation and 43(17) per cent within 1 h before surgery ( P  = 0.024); in fasted controls it was 2(4) per cent ( P  < 0·001). After surgery, cyclic motor patterns increased markedly in extent and intensity, becoming nearly continuous (active duration 94(13) per cent; P  < 0·001), with peak frequency 2–4 cycles per min in the sigmoid colon. This postoperative cyclic pattern was substantially more prominent than in non‐operative controls, including in the fed state (active duration 27(20) per cent; P  < 0·001), and also showed higher antegrade velocity ( P  < 0·001). Conclusion: Distal gut motility becomes markedly hyperactive with colonic surgery, dominated by cyclic motor patterns. This hyperactivity likely represents a novel pathophysiological aspect of the surgical stress response. Hyperactive motility may contribute to gut dysfunction after surgery, potentially offering a new therapeutic target to enhance recovery. Abstract : May contribute to gut dysfunction